2003
DOI: 10.1108/13612020310464340
|View full text |Cite
|
Sign up to set email alerts
|

Fashion innovativeness, fashion diffusion and brand sensitivity among adolescents

Abstract: Using Rogers' theory of diffusion of innovation, this paper reports the results of a study that had two objectives: the first objective was to compare the number of male and female adolescents in each of Rogers' five categories of consumer adopters. The second, was to verify if there were differences among the five distinct categories of adopters with respect to brand sensitivity. Results show that, as with other market segments, there are more female than male adolescents in the categories``innovators'' and``… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 11 publications
3
52
0
Order By: Relevance
“…Behling (1992) stated that fashion innovative consumers tend to be female, higher in education, younger in age, very social, high in self-confidence, and financially stable. Other studies confirmed that typically female consumers more than male consumers are fashion innovative (Beaudoin et al, 2003;Goldsmith et al, 1987).…”
Section: Gender and Fashion Innovativenessmentioning
confidence: 91%
See 3 more Smart Citations
“…Behling (1992) stated that fashion innovative consumers tend to be female, higher in education, younger in age, very social, high in self-confidence, and financially stable. Other studies confirmed that typically female consumers more than male consumers are fashion innovative (Beaudoin et al, 2003;Goldsmith et al, 1987).…”
Section: Gender and Fashion Innovativenessmentioning
confidence: 91%
“…Demographic (e.g., age and gender) and psychographic characteristics (e.g., shopping styles and opinion leadership) have been found to affect search behavior and brand preference/choice (e.g., Beaudoin & Lachance, 2006;Beaudoin, Lachance, & Robitaille, 2003;Hogg, Bruce, & Hill, 1998;Nysveen, Pedersen, & Thorbjørnsen, 2005).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only as a result of consumers' choices -and trendsetters' choices in particular -to buy and wear garments will certain garments come to be in fashion and others not (cf. Beaudoin et al, 2003). No one is in total control of the social game being played, especially since actions are seldom made in concert.…”
Section: Acta Sociologica 51(3)mentioning
confidence: 99%